Penilaian Daya Dukung untuk Penguatan Tata Kelola Konservasi Lanskap: Studi Kasus Sub-Daerah Aliran Sungai Danau Sentarum - Indra Kumara; Rinekso Soekmadi; Lilik B. Prasetyo; Arzyana Sunkar; Dwi Kusharyono (Jurnal Penelitian Pendidikan IPA, 2026)
A landscape carrying capacity assessment serves as a critical tool for strengthening sustainable natural resource governance within socio-ecological systems. This study aimed to evaluate the carrying capacity status of the Sentarum Lake Catchment Area and identify key ecological and socioeconomic vulnerabilities. The analysis was conducted using a multi-criteria index-based approach aligned with the Indonesian Minister of Forestry Regulation No. P.61/Menhut-II/2014, integrating cross-sectoral data across five dimensions: land condition, water regime, socioeconomic conditions, water infrastructure, and land use patterns. The results showed that the carrying capacity was classified as “good,” with an index value of 78.00. Nevertheless, a phenomenon of pseudo-hydrological stability was identified, in which stable flow regimes (flow regime coefficient = 0.50) and high water availability (water use index = 0.50) masked functional degradation within the system. This condition was reflected in a high annual runoff coefficient (1.50) and increasing flood frequency (1.25), indicating declining infiltration capacity. These pressures were further exacerbated by the limited proportion of natural vegetation within protected areas (45.10%) and high socioeconomic vulnerability (poverty level index = 1.50). Overall, the findings indicate a fragile equilibrium in which apparent ecological stability conceals emerging hydrological and socioeconomic risks. Without adaptive and integrated management interventions, the system is likely to shift toward structural degradation. Therefore, strengthening landscape governance requires ecosystem-based spatial planning, nature-based mitigation strategies, and inclusive local economic development to enhance long-term resilience.